Kerjasama Orang Tua dan Guru PAI Dalam Memotivasi Siswa Menghafal al-Qur'an - Robi Aksyhari, dkk. (Program Studi Pendidikan Agama Islam, 2020)
This study aimed at finding out the portrayal of cooperation between parents and teachers in providing motivation for students to memorize al-Qur’an as a program of SDN 05 in Bermani Ulu district, Rejang Lebong, Bengkulu. This study used a qualitative approach. The data were collected using observation and interview techniques. After the data were collected, the next step was to select the data, present the data, and draw conclusion. The conclusion got based on the study indicated that the form of cooperation between teachers of SDN 05 in Bermani Ulu district, Rejang lebong, and parents was built up in ways of establishing communication with one another, giving guidance and controlling at home, motivating students in every way, and working together to make Qur’an memorization competition for students at school on Islamic big days.